IMPROVING STUDENTS’ ABILITY ON READING THROUGH LANGUAGE EXPERIANCE APPROACH AT PRIMARY SCHOOL OF HADOMUAN 173187 GRADE FIVE - Ayu Lestari Simatupang; Kammer Tuahman Sipayung (Jurnal Scientia, 2023)
Reading is an activity done to get message to conveyed by the author through the medium of words or standard language. The aim of this study is to improve the ability of students reading at Primary school of Hadomuan 173187 Grade Five. To achieve the aim of this study, the researcher applied classroom action research method. Population of this study is fourty three students and sample of this study is eighteen students.The data were analyzed qualitatively and quantitatively through reading test . This research shown that the first cycle indicat that there were some students or (94%) who get below of minimum standard ( under 70) and above of minimum standard is 6%. The second cycle indicated that all student achive above of minimum standard is 100%. It can be concluded that language experience approach able to improve the students reading ability. It can be as an alaternative way in teaching reading for primary school at Hadomuan 173187.